Pengaruh Laba Bersih, Hutang Bank & Arus Kas Operasi Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2013 – 2015 - Widjanarko Widjanarko; Nurmelia Safitri (Jurnal Akuntansi Dan Bisnis Indonesia (JABISI), 2020)
The Objective of this research to know the infuence of net profit, bank credit and the cashflow have a significant influence to divident payout in the manufacturing company that listing at the Indonesia Stock Exchange in 2013-2015. Data that used in this research using secondary data that published in website www.idx.co.id. It used the quantitative analysis method to do this research, by statistics like regression analysis and test of classic assumption. The result of this research show that the net profit, bank credit and the cashflow influenced the dividen Payout.